Woman to Woman: Australian Feminists' Embrace of Radio Broadcasting, 1930s–1950s. Issue 93 (3rd July 2017) - Baker, Jeannine
ABSTRACT: This article demonstrates the crucial importance of the radio medium in the post-suffrage era as a space in which women could expand their sphere of influence and enact their responsibilities as citizens. It challenges previous scholarship which has argued that during the early decades of radio women were confined to the world of the everyday and the domestic. In the interwar years, Australian feminist organisations were quick to take advantage of the still-developing radio medium, which they used to publicise their activities to mass audiences. One such organisation was the United Associations (UA), founded in Sydney in 1929 by Jessie Street and Linda Littlejohn. Perth feminist Irene Greenwood was introduced to radio broadcasting as a member of the UA in the 1930s, and she later drew on these media skills and her extensive feminist networks to create her own innovative and interactive radio program in Western Australia, Woman to Woman (1948–1954). Correspondence between Greenwood and her audience shows that the program provided women from diverse backgrounds with the opportunity to engage publicly with significant political debates, to create a new imagined community of listeners, to communicate across geographical and class boundaries, and to become media producers themselves.